Relationship of low molecular weight fluorophore levels with clinical factors and fenofibrate effects in adults with type 2 diabetes - Januszewski, Andrzej S. (2021)
People with diabetes are at risk of chronic complications and novel biomarkers, such as Advanced glycation end-products (AGEs) may help stratify this risk. We assessed whether plasma low-molecular weight AGEs, also known as LMW-fluorophores (LMW-F), are associated with risk factors, predict complications, and are altered by fenofibrate in adults with type 2 diabetes. Plasma LMW-F were quantified at baseline, after six weeks fenofibrate, and one year post-randomisation to fenofibrate or placebo. LMW-F associations with existing and new composite vascular complications were determined, and effects of fenofibrate assessed. LMW-F correlated positively with age, glycated haemoglobin (HbA1c), pulse pressure, kidney dysfunction and inflammation; and negatively with urate, body mass index, oxidative stress and leptin, albeit weakly (r = 0.04-0.16, all p < 0.01). Independent determinants of LMW-F included smoking, diastolic blood pressure, prior cardiovascular disease or microvascular complications, Caucasian ethnicity, kidney function, HbA1c and diabetes duration (all p ≤ 0.01). Baseline LMW-F tertiles correlated with on-trial macrovascular and microvascular complications (trend p < 0.001) on univariate analyses only. Six weeks of fenofibrate increased LMW-F levels by 21% (p < 0.001). In conclusion, LMW-F levels correlate with many risk factors and chronic diabetes complications, and are increased with fenofibrate. LMW-F tertiles predict complications, but not independently of traditional risk factors.